Becoming a university student: An emotional rollercoaster - Perander, Katarina; Londen, Monica; Holm, Gunilla; Tiihonen, Susanne (Högre utbildning, 2020)
Students’ experiences during their first year of higher education affect study pace, retention and graduation. The aim of this study was to examine how students describe and perceive their studying and academic emotions during the first semester of higher education in order to analyse the interplay of different factors affecting student learning. The students participated in a compulsory study skills course, and wrote about their study experiences in reflective journals (N = 190) that were analysed qualitatively. Reflective journals have been rarely used in previous research on first year studies. The journals allow students to write about their experiences as a whole, and provide a broad and in-depth picture of students’ perceptions of their study habits and learning in higher education. Our results revealed that students’ academic emotions were profoundly affected by their self-regulated learning skills. Moreover, the study showed how self-regulated learning and academic emotions were tightly intertwined. In order to enhance student learning both self-regulated learning and academic emotions need to be considered in university teaching, and when universities plan the first year for new students.